Myofibroblasts revert to an inactive phenotype during regression of liver fibrosis - Tatiana Kisseleva; Min Cong; Yong‐Han Paik; David Scholten; Chunyan Jiang; Christopher Benner; Keiko Iwaisako; Thomas Moore‐Morris; Brian T. Scott; Hidekazu Tsukamoto; Sylvia Μ. Evans; Wolfgang Dillmann; et al. (2012)
Myofibroblasts produce the fibrous scar in hepatic fibrosis. In the carbon tetrachloride (CCl(4)) model of liver fibrosis, quiescent hepatic stellate cells (HSC) are activated to become myofibroblasts. When the underlying etiological agent is removed, clinical and experimental fibrosis undergoes a remarkable regression with complete disappearance of these myofibroblasts. Although some myofibroblasts apoptose, it is unknown whether other myofibroblasts may revert to an inactive phenotype during regression of fibrosis. We elucidated the fate of HSCs/myofibroblasts during recovery from CCl(4)- and alcohol-induced liver fibrosis using Cre-LoxP-based genetic labeling of myofibroblasts. Here we demonstrate that half of the myofibroblasts escape apoptosis during regression of liver fibrosis, down-regulate fibrogenic genes, and acquire a phenotype similar to, but distinct from, quiescent HSCs in their ability to more rapidly reactivate into myofibroblasts in response to fibrogenic stimuli and strongly contribute to liver fibrosis. Inactivation of HSCs was associated with up-regulation of the anti-apoptotic genes Hspa1a/b, which participate in the survival of HSCs in culture and in vivo.